The implications for the Aragonese child protection system of Law 3/2024 amending the Aragonese Foral Code concerning legal capacity of individuals - López Azcona, Aurora (Revista de derecho aragonés, 2024)
The extensive reform of Aragonese civil law enacted through Law 3/2024, which amends the Aragonese Foral Code concerning the legal capacity of individuals, extends beyond merely aligning its provisions on disability with the 2006 UN Convention on the Rights of Persons with Disabilities. Concurrently, it has undergone a thorough revision of its framework for the protection of minors. It is therefore crucial to provide a detailed analysis of the new provisions introduced by the reform, both those pertaining to capacity based on age and those related to the various private and public mechanisms that structure the protection of minors within the Aragonese legal system.
Keywords: Child protection; Aragonese civil law; Capacity by reason of age; Guardianship institutions; Protection of minors by the Administration